Diversidade genética de norovírus, co-infecções e status nutricional de crianças em estudo caso-controle no semiárido brasileiro - Gondim, Rafhaela Nogueira Della Guardia (2017)
Norovirus (NoV) infection is a major global health problem with high incidence morbid-mortality rates. However, the impact of NoV on child development remains poorly described. We wanted to investigate the genetic diversity of circulating NoV strains in children from the semiarid region of Brazil, and its associations with other co-infections and clinical/nutritional status. This case-control study was conducted in six different cities with children aged 2-36 months during the period from April 2010 to March 2011. Cases considered were children who had at least one episode of diarrhea in the last 14 days. Detection and quantification of NoV were performed by RT-qPCR, followed by molecular and phylogenetic analysis. The presence of NoV was 45.2% (75/166), and ranged from 8–77.7% among the cities examined. A lower z-score index was associated with the presence of NoV with weight for age – WAZ (P = 0.034), weight for height – WHZ (P= 0.033), and body mass index for age – BAZ (P = 0.033). In addition, NoV infection was associated with more frequent respiratory symptoms (P= 0.0096). GII.P7 (polymerase genotype) and GII.3 (capsid genotype) were the most frequent NoV genotypes, and analysis of the ORF 1-2 junction identified recombinant NoV strains in 80% (12/15) of the sequenced samples. With regards to co-infections, infections with enteroaggregative Escherichia coli (P = 0.0046) were more frequent in the absence of NoV, whereas in the presence of Shigella a positive correlation was observed with NoV (P = 0.0199). Among the positive cases of NoV, diarrheal episodes were associated with the presence of entero-aggregative E. coli, and simultaneous absence of Cryptosporidium and shiga toxin-producing E. coli (P = 0.0167). The present study highlighted the high genetic variability of NoV in the semiarid region of Brazil, and underlines its role in co-infections and infant nutritional status, thus contributing to better understandings of its impact on infant development and its